KEMAMPUAN BERPIKIR ALJABAR SISWA SMP PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL (SPLDV) - Ida Farida; Dori Lukman Hakim (IKIP Siliwangi, 2021)
Algebraic thinking skills are very important to be mastered by students, by thinking algebra students can better understand and solve problems that occur in daily life, especially problems related to the form of algebra. The research aims to analyze and describe the algebraic thinking ability of junior high school students in solving problems in SPLDV material. This research was conducted at SMP Negeri 2 Karawang Barat School Year 2020/2021, with the subject of the study as many as 30 junior high school students in grade VIII. The method used in this study is descriptive qualitative, with instruments in the form of description tests as many as 2 SPLDV questions and documentation. The data analysis techniques in this study were conducted by reducing data, presenting data, and drawing conclusions. From the results of the study found that there are still many students who have not been able to meet the Graduate Competency Standards that indicate that students' algebraic thinking ability is still low, it is due to the lack of understanding of students about the concept of algebra. Evidently, from 2 points of algebra thinking given to students obtained percentage data of 20% of students thinking high algebra, 16.67% of students thinking moderate algebra and 13.33% of students thinking low algebra.